Interrelationships with Metabolic Syndrome, Obesity and Cardiovascular Risk - Said, Sarmad; Mukherjee, Debabrata; F. Whayne, Thomas (Current Vascular Pharmacology, 2016)
Cardiovascular (CV) disease is the most common cause of morbidity and mortality worldwide, particularly in the presence of the metabolic syndrome (MetS). Classifications and treatment of the MetS have recently been redefined. While the majority of the cardiac components such as hypertension, diabetes mellitus (DM) and dyslipidemia (DLD) are objectively measurable elements, a few disparities among the definitions have to be considered that can variably modify diagnosis, treatment and prevention. Non-cardiac factors such as liver disease (including, but not limited to, alcoholic and non-alcoholic steatosis/hepatitis), renal disease, severe obesity, polycystic ovarian syndrome and obstructive sleep apnea (OSA), may have independent or synergistic relationship with complementary cardiac MetS elements, and these additional risk factors may have an incremental adverse impact on CV outcome. The combination of all these factors potentiates the adverse significance on CV events. MetS not only increases morbidity and mortality but also has economic ramifications for the healthcare system. Prevention of CV disease includes primary and secondary aspects. Besides overall advances to provide optimal care for hypertension, diabetes, and dyslipidemia, early-targeted inventions to diagnose, treat and prevent OSA, and severe obesity, are needed.
Keywords: obesity